TINDAK TUTUR EKSPRESIF GURU DAN PESERTA DIDIK DALAM PROSES PEMBELAJARAN DI TK IT AL-BIRUNI MANDIRI JIPANG DI KOTA MAKASSAR (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to describe the forms of expressive speech acts of teachers and students as well as describe the strategies of teacher speech acts towards students in the learning process at Al-Biruni Mandiri Jipang IT Kindergarten in Makassar City. Type of descriptive qualitative research. Data in the form of written data from voice recordings. The data source is teacher and student speech. Data collection techniques use listening, documentation and note-taking The results of the research revealed that there were 11 expressive speech acts by teachers and 1 expressive speech act by students and 6 strategies were found by teachers in the learning process.